The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000448624
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias for Emotional Stimuli in Borderline Personality Disorder: A Meta-Analysis

Abstract: Background: In borderline personality disorder (BPD), attentional bias (AB) to emotional stimuli may be a core component in disorder pathogenesis and maintenance. Sampling: 11 emotional Stroop task (EST) studies with 244 BPD patients, 255 nonpatients (NPs) and 95 clinical controls and 4 visual dot-probe task (VDPT) studies with 151 BPD patients or subjects with BPD features and 62 NPs were included. Methods: We conducted two separate meta-analyses for AB in BPD. One meta-analysis focused on the EST for general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 52 publications
1
30
1
3
Order By: Relevance
“…Subsequently, continuous reorientation and/or slowed disengagement might interfere with cognitive resources required to disengage attention from sensory salient but behaviorally irrelevant stimuli. This is in line with behavioral studies, reporting on biased attention towards emotional stimuli in BPD (Arntz et al 2000;von Ceumern-Lindenstjerna et al 2010;Kaiser et al 2016;Bertsch et al 2017). Additional evidence is provided by previous fMRI studies using attention tasks, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, continuous reorientation and/or slowed disengagement might interfere with cognitive resources required to disengage attention from sensory salient but behaviorally irrelevant stimuli. This is in line with behavioral studies, reporting on biased attention towards emotional stimuli in BPD (Arntz et al 2000;von Ceumern-Lindenstjerna et al 2010;Kaiser et al 2016;Bertsch et al 2017). Additional evidence is provided by previous fMRI studies using attention tasks, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Some research indicating that people with BPD are particularly prone to rumination, for example, suggests difficulty disengaging from emotional events (Abela, Payne, & Moussaly, 2003; Smith, Grandin, Alloy, & Abramson, 2006), and the cascade model of BPD posits that NSSI is particularly likely when rumination has amplified negative emotional experiences to an intolerable level (Selby & Joiner, 2009). Findings from some studies have suggested the presence of an attentional bias toward negative and BPD-related stimuli (words; Kaiser, Jacobs, Domes, & Arntz, 2017); this possible bias may amplify emotional responding and disrupt the ability of persons with BPD to disengage or distance themselves from emotional events. The findings on attentional biases in BPD, however, are complex, sometimes inconsistent, and may depend on the laboratory paradigms and stimuli used (Kaiser et al, 2017).…”
Section: Characteristics Of Ed In Adults With Bpdmentioning
confidence: 99%
“…Findings from some studies have suggested the presence of an attentional bias toward negative and BPD-related stimuli (words; Kaiser, Jacobs, Domes, & Arntz, 2017); this possible bias may amplify emotional responding and disrupt the ability of persons with BPD to disengage or distance themselves from emotional events. The findings on attentional biases in BPD, however, are complex, sometimes inconsistent, and may depend on the laboratory paradigms and stimuli used (Kaiser et al, 2017).…”
Section: Characteristics Of Ed In Adults With Bpdmentioning
confidence: 99%
“…Further operationalization included a faster orientation towards negative emotional faces. A meta-analysis conducted by Kaiser and colleagues [14] partially supported Linehan’s hypersensitivity hypothesis by revealing negative attentional bias for BPD schema congruent words and moderate attentional bias for positive emotional faces. Moreover, a recent work from Kaiser and colleagues [15] extended the previous findings [14] showing that BPD attentional bias was enhanced for threating information.…”
Section: Introductionmentioning
confidence: 98%